STUDI PENGGUNAAN KOMUNIKASI EFEKTIF DALAM LINGKUNGAN KELUARGA DAN PENDIDIKAN ANAK USIA DINI : A STUDY ON THE USE OF EFFECTIVE COMMUNICATION IN FAMILY ENVIRONMENTS AND EARLY CHILDHOOD EDUCATION - Juwita, Ratna; Aziz Wahab, Abd.; Kiromi, Ivonne Hafidlatil (Universitas Islam Malang, 2023)
Communication in human life is very important. For young children how to communicate is a challenge to live their lives, so early childhood must learn how to communicate, especially effective communication both in the family and social environment, because there are already many children who are still at an early age the way of communication is less effective because it is influenced by several factors which exists. This research aims to increase knowledge for adults or parents how to communicate with early childhood effectively. The subjects of this study are adults who will implement effective communication for early childhood. In our research using library research (Library Research). Library research is the activity of collecting materials related to research from scientific journals, literature and authors. The results of the study show that in the family environment the way to communicate with early childhood is by respecting each other, understanding each other, adjusting communication styles and guiding children in terms of good communication. Whereas in early childhood education the teacher must be a good communicator, understand the characteristics of students, provide a comfortable and safe atmosphere and the teacher must be able to form close relationships with students in order to make it easier for students to communicate with teachers so as to build effective communication. By implementing effective communication from an early age, children will be able to interact with their social environment, be able to express their feelings and children will be able to develop their language when communicating.